Causal Responsibility and Robust Causation - Grinfeld, Guy; Lagnado, David; Gerstenberg, Tobias; Woodward, James F.; Usher, Marius (Frontiers in Psychology, 2020)
How do people judge the degree of causal responsibility that an agent has for the effects of her actions? We show that a relatively unexplored factor – the robustness (or stability) of the causal chain linking the agent’s action and the effect – influences judgments of causal responsibility of the agent. In three experiments, we vary robustness by manipulating the number of background circumstances under which the action causes the effect, and find that causal responsibility judgments increase with robustness. In the first experiment, the robustness manipulation also raises the probability of the effect given the action. Experiments 2 and 3 control for probability-raising, and show that robustness still affects judgments of causal responsibility. In particular, Experiment 3 introduces an Ellsberg type of scenario to manipulate robustness, while keeping the conditional probability and the skill deployed in the action fixed. Experiment 4, replicates the results of Experiment 3, while contrasting between judgments of causal strength and of causal responsibility. The results show that in all cases, the perceived degree of responsibility (but not of causal strength) increases with the robustness of the action-effect link.